Endocrine and Metabolic Signaling in Retroperitoneal White Adipose Tissue Remodeling during Cold Acclimation - Aleksandra Jankovic; Aleksandra Korac; Biljana Buzadzic; Vesna Otasevic; Ana Stancic; Milica Vucetic; Milica Markelic; Ksenija Velickovic; Igor Golic; Bato Korac (Journal of Obesity)
The expression profiles of adiponectin, resistin, 5′-AMP-activated protein kinase α (AMPKα), hypoxia-inducible factor-1α (HIF-1α), and key enzymes of glucose and fatty acid metabolism and oxidative phosphorylation in rat retroperitoneal white adipose tissue (RpWAT) during 45-day cold acclimation were examined. After transient suppression on day 1, adiponectin protein level increased following sustained cold exposure. In parallel, on day 1, the protein level of HIF-1α was strongly induced and AMPKα suppressed, while afterwards the reverse was seen. What is more, after an initial decrease on day 1, a sequential increase in pyruvate dehydrogenase, acyl-CoA dehydrogenase, cytochrome c oxidase, and ATP synthase and a decrease in acetyl-CoA carboxylase (from day 3) were observed. Similar to adiponectin, protein level of resistin showed a biphasic profile: it increased after days 1, 3, and 7 and decreased below the control after 21 days of cold-acclimation. In summary, the data suggest that adiponectin and resistin are important integrators of RpWAT metabolic response and roles it plays during cold acclimation. It seems that AMPKα mediate adiponectin effects on metabolic remodeling RpWAT during cold acclimation.